MASA KERJA DAN SUBJECTIVE WELL-BEING (STUDI TERHADAP GURU SLB BAGIAN B DAN C BAGASKARA SRAGEN) - Wulandari, Tyas (Jurnal Aspirasi, 2013)
Education and quality teachers are important in Indonesia, because the quality of special-ed teacher who was instrumental in improving the quality of students. This study aims to illustrate the condition of subjective well-being (SWB) in the special-ed teacher. The study involved 22 special-ed teacher sections B and C Bagaskara Sragen. Research methods using descriptive quantitative approach to data analysis using Crosstab analysis. As a method of support do interviews and observations in the field prior to the study. The results showed that the SWB condition cannot be determined time of work from teachers. Where the Subjective well-being (SWB) in overall teacher is at high categorization. There are a number of environmental factors that can affect the condition of individual SWB, among other things: autonomy, self-control and have an understanding of self, environmental mastery, purpose in life, positive relations (warm) with others and self-acceptance.